Association between the perceived environment and overweight in adults and elderly: a cross-sectional study. Issue 1 (December 2016) - Matozinhos, Fernanda; Gomes, Crizian; Mendes, Larissa; Pessoa, Milene; Padez, Cristina; das Graças Pena, Geórgia; Velasquez-Melendez, Gustavo
Abstract Background Overweight is a global issue of epidemic proportions, and its negative influence on individual health is clear. However, the relation between environment and overweight is not thoroughly clear, especially concerning to the perceived environment and the physical and social aspects. Therefore, this study aimed to analyze potential associations between the perceived environment and overweight in adults and elderly in a medium-sized city. Methods A cross-sectional population-based study was conducted with 808 adult and elderly individuals. Overweight was defined as body mass index ≥25 kg/m2 based on the World Health Organization criteria. The Neighborhood Environment Walkability Scale was used evaluating the perceived environment. Poisson regression was performed evaluating the relationships between the perceived environment and overweight. Results The frequency of overweight was 50.4 %. Adjusted models showed association between overweight and the variable of surrounding neighborhood as follows: "1- to 3-story apartments or condos" (most category; PR = 0.30; CI 0.12–0.76) and "4- to 6-story apartments or condos" (all categories) (PR ranged 0.40 to 0.46;p  < 0.05), and also, "land-use mix-diversity" was associated with overweight in this population (PR 0.81; CI 0.66–0.99). Conclusions In addition to individual characteristics, the environmental aspects are relevant to the occurrence of overweight in this population. Population-based studies using primary data on overweight remain scarce in Brazil. Finally, this study contributes to improve the understanding of the complex relationship between perceived environment and overweight, and we believe that our findings provide further justification for the development of future interventions and health promotion strategies.